1989
DOI: 10.7589/0090-3558-25.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selected Anthelmintics on Three Common Helminths in the Brown Pelican (Pelecanus occidentalis)

Abstract: The effect of selected anthelmintics (albendazole, fenbendazole, piperazine dihydrochloride and clorsulon) against three major helminths (Contracaecum multipapillatum, Mesostephanus appendiculatoides, and Phagicola longus) were studied in 29 brown pelicans (Pelecanus occidentalis). Albendazole and fenbendazole were highly effective against all three parasites. Clorsulon had moderate effect against M. appendiculatoides and poor effect against C. multipapillatum and P. longus. Piperazine dihydrochloride had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…They are common parasites of the gut and proventriculus of waterbirds, often causing pathological lesions in their hosts (Huizinga, 1971;Fagerholm et al, 1996;Abollo et al, 2001;Dezfuli et al, 2002). Among the species of Contracaecum considered as valid by Hartwich (1964), C. rudolphii Hartwich, 1964 (sensu lato) (see Hartwich, 1964), C. multipapillatum (von Drasche, 1882) (see Lucker, 1941), C. micropapillatum (Stossich, 1890) and C. microcephalum (Rudolphi, 1809) have been recorded as parasites of various fish-eating birds from the Western Hemisphere (Huizinga, 1971;Courtney & Forrester, 1974;Grimes et al, 1989;Humphrey et al, 1978;Deardoff & Overstreet, 1980;Dyer et al, 2002;Navone et al, 2000;Dronen et al, 2003;Torres et al, 2005). In addition, C. mexicanum Flores- Barroeta, 1957 has been described from Pelecanus occidentalis (L.) near Acapulco, Mexico (Flores- Barroeta, 1957) and later reported from the same host in Central America by Dyer et al (2002).…”
Section: Introductionmentioning
confidence: 98%
“…They are common parasites of the gut and proventriculus of waterbirds, often causing pathological lesions in their hosts (Huizinga, 1971;Fagerholm et al, 1996;Abollo et al, 2001;Dezfuli et al, 2002). Among the species of Contracaecum considered as valid by Hartwich (1964), C. rudolphii Hartwich, 1964 (sensu lato) (see Hartwich, 1964), C. multipapillatum (von Drasche, 1882) (see Lucker, 1941), C. micropapillatum (Stossich, 1890) and C. microcephalum (Rudolphi, 1809) have been recorded as parasites of various fish-eating birds from the Western Hemisphere (Huizinga, 1971;Courtney & Forrester, 1974;Grimes et al, 1989;Humphrey et al, 1978;Deardoff & Overstreet, 1980;Dyer et al, 2002;Navone et al, 2000;Dronen et al, 2003;Torres et al, 2005). In addition, C. mexicanum Flores- Barroeta, 1957 has been described from Pelecanus occidentalis (L.) near Acapulco, Mexico (Flores- Barroeta, 1957) and later reported from the same host in Central America by Dyer et al (2002).…”
Section: Introductionmentioning
confidence: 98%
“…The following species of Contracaecum have been reported from the brown pelican P. occidentalis (L.) in the Gulf of Mexico and the Caribbean Sea: C. mexicanum Flores Barroeta, 1957from off Venezuela and Puerto Rico (Diaz-Ungria, 1978, 1979Dyer et al, 2002); C. multipapillatum (Drasche, 1882) in the Gulf of Mexico (Courtney & Forrester, 1974;Courtney et al, 1977;Deardorff & Overstreet, 1980;Grimes et al, 1989) and off Puerto Rico (Dyer et al, 2002); C. rudolphii Hartwich, 1964(sometimes reported as C. spiculigerum Rudolphi, 1809 in the Gulf of Mexico (Hutton, 1964;Huizinga, 1966Huizinga, , 1971Courtney & Forrester, 1974;Deardorff & Overstreet, 1980) and off Puerto Rico (BunkleyWilliams & Williams, 1994); C. bioccai Mattiucci, Paoletti, Olivero-Verbel, Baldiris, Arroyo-Salgado, Garbin, Navone & Nascetti, 2008 from off northern Colombia. Undetermined species have also been reported, as Contracaecum sp.…”
Section: Introductionmentioning
confidence: 96%
“…Garvin et al (2006), examining blood parasites of Nearctic-Neotropical Passerines during spring migration in the Gulf coast, found that 21 % of 1,705 migrant Passerines were infected with one or more blood parasites. Helminth (parasitic worms) infections are quite common in Brown Pelicans along the Gulf coast, and although the effects of infections are unclear at times (Dyer et al 2002), stressed pelicans can show the effects of parasitism (Grimes et al 1989;Dronen et al 2003). Similarly, 22 species of endohelminths were found in Willets collected from Texas (Dronen et al 2002), and several platyhelminthes species (Clinostomum sp., Mesotephanus sp., Galactosomum sp.)…”
Section: Parasites and Diseasementioning
confidence: 99%